Dr. Seuss': The Grinch - Meledandri, Chris; Healy, Janet; LeSieur, Michael; Swerdlow, Tommy; Cheney, Yarrow; Mosier, Scott; Cumberbatch, Benedict, 1976-; Jones, Rashida; Lansbury, Angela, 1925-; Thompson, Kenan; Seuss, Dr.; Universal Pictures Corporation; et al. (Universal City, CA : Universal Pictures Home Entertainment, 2019)
The story of a cynical grump who goes on a mission to steal Christmas, only to have his heart changed by a young girls generous holiday spirit. It is a universal story about the spirit of Christmas and the indomitable power of optimism.
Based on Dr. Seuss beloved holiday classic.
Originally released as a motion picture in 2018.
Wide screen.
Special features: The making of the mini-movies; From green to screen; Whos who in Who-ville; My earliest Grinch memories; "Youre a mean one, Mr. Grinch" lyric video; Songs from his little heart; Grinchy gadgets; Any who can draw: The Grinch, Max, Fred; Cindy-Lous yule log and more.
Keywords: Grinch (Fictitious character) -- Drama; Generosity -- Drama; Feature films; Childrens films; Comedy films; Animated films